To study and analyze the relationship between ethical factors and stakeholder responsibility with the financial performance of organizations. - จิรอุดมสาโรจน์, พัทธ์ธีรา; แสงอาวุธ, เพ็ญจันทร์; อุสันเทียะ, อรจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aims to analyze the relationship between ethical factors and accountability to stakeholders with the financial performance of organizations. It employs Multiple Regression Analysis to evaluate the effects of independent variables, including transparency, independence, fairness, and integrity (X1), competence and work standards (X2), accountability to service recipients and confidentiality (X3), and accountability to shareholders, partners, or individuals or entities to whom accounting professionals provide services (X4) on the financial performance of the organization. Fairness and honesty (X1), knowledge, competence, and work standards (X2), responsibility towards service users and confidentiality (X3), and responsibility towards shareholders, partners, or individuals or entities to whom the accounting professional provides services (X4) on the organization's financial performance.The research findings indicate that ethical factors such as transparency, responsibility towards service recipients, and accountability towards shareholders and stakeholders have a statistically significant positive relationship with the organization's financial performance. In contrast, factors related to knowledge, competence, and operational standards do not show a significant relationship with financial performance. The study's conclusion suggests that promoting and developing ethical factors and accountability to stakeholders should be used as a key guideline in developing organizational strategies to enhance financial performance.The study's conclusion suggests that promoting and developing ethical factors and responsibility towards stakeholders should be used as a key guideline in developing organizational strategies to enhance financial performance.